2019
DOI: 10.2196/13667
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Robot Attentional Behaviors on User Perceptions and Behaviors in a Simulated Health Care Interaction: Randomized Controlled Trial

Abstract: BackgroundFor robots to be effectively used in health applications, they need to display appropriate social behaviors. A fundamental requirement in all social interactions is the ability to engage, maintain, and demonstrate attention. Attentional behaviors include leaning forward, self-disclosure, and changes in voice pitch.ObjectiveThis study aimed to examine the effect of robot attentional behaviors on user perceptions and behaviors in a simulated health care interaction.MethodsA parallel randomized controll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…ref. [20,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]); however, evidence is limited regarding how people's subjective perceptions of self-disclosure align with objective measures of self-disclosure. Here we evaluate both people's perceptions and their actual disclosures across three experiments.…”
Section: Subjective and Objective Disclosurementioning
confidence: 99%
“…ref. [20,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]); however, evidence is limited regarding how people's subjective perceptions of self-disclosure align with objective measures of self-disclosure. Here we evaluate both people's perceptions and their actual disclosures across three experiments.…”
Section: Subjective and Objective Disclosurementioning
confidence: 99%
“…In another study, Mumm and Mutlu (2011) manipulated a robot into either likable (a polite, empathetic 20-second monologue during the introduction) or unlikable (a rude, selfish monologue) behavior and found people answered more sensitive questions from the likeable robot. In a most recent study, Johanson et al (2019) found that a health care robot using self-disclosure and a forward lean increased human engagement and attentional behaviors. These studies not only provide a glimpse of the possible effect of different robot disclosures on human anxiety toward the robot and disclosure behavior, they also support the CASA framework which suggests that people attribute verbal communication from a social robot to inform their own perception of the robot and their behavior toward it.…”
Section: Self-disclosure In Human-robot Interactionmentioning
confidence: 99%
“…Last but not least, soft and flexible robots for medical applications are needed to change their flexibility over a wide range to perform tasks adequately [ 127 ], so as to acupuncture robot. Those technologies include a spatially resolved soft sensor for biomechanics and robotic haptic capability which may lead to better interaction between patients and the robot [ 128 ]; also, the use of self-disclosure and forward lean by a healthcare robot can increase human engagement and attentional behaviors [ 129 ]. More intelligent components would be integrated in order to achieve integration of a plurality of functions required in medical acupuncture applications.…”
Section: Discussionmentioning
confidence: 99%